Literatur Review :Analisis Mengenai Facebook - GRADIANI, SIMFROSA GRADIANI (Universitas Ngudi Waluyo, 2024)
Abstrack Facebook has far more than 2.91 billion users worldwide, as of October 2021 by following its commitment to “Give people the power to build community and bring the world closer together”. May of Facebook, major acquisition of Facebook, applications of AI in Facebook and Financial plans and challenges. The entire Facebook company will now be known as Meta. The Facebook app, on the other hand, will keep its name, and other apps will not be affected. Facebook is now known as 'Meta' because of its new focus which means 'after' or 'beyond' in Greek. However, Instagram, Facebook, WhatsApp, and Messenger are now all part of the 'Meta' company, much like Google's products are all part of the Alphabet company. Artificial intelligence, AI is really essential to Facebook. Keyword: Facebook, Meta, Machine learning